If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 14 = 16 + -10x Reorder the terms: 14 + 5x = 16 + -10x Solving 14 + 5x = 16 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 14 + 5x + 10x = 16 + -10x + 10x Combine like terms: 5x + 10x = 15x 14 + 15x = 16 + -10x + 10x Combine like terms: -10x + 10x = 0 14 + 15x = 16 + 0 14 + 15x = 16 Add '-14' to each side of the equation. 14 + -14 + 15x = 16 + -14 Combine like terms: 14 + -14 = 0 0 + 15x = 16 + -14 15x = 16 + -14 Combine like terms: 16 + -14 = 2 15x = 2 Divide each side by '15'. x = 0.1333333333 Simplifying x = 0.1333333333
| 0.25(2x+1)-1/x-1=x/2 | | 4(x+1)2-2(2x-5)(x+2)=0 | | 15u^2+u-2=0 | | (x+3)-(2x-7)+6=13(x-1)+4(2x+1)-7x | | x+5/3-18-2x/4=x+3/6 | | (2k+5/4)=2-(k+2/3) | | (7k/4)=2-(2k/3) | | (4x+1)(3x+6)= | | 1/5x+1/11(x+14) | | 3x-2Y=150 | | 2.9x=27.55 | | 4.8x=40.8 | | 24x^3+36x^2= | | 3X=2Y+150 | | 2x+12=12-10x | | x(-15x-64)-33=0 | | -9-6x=5x+14 | | (x+3/3)-(x-1/2)=4 | | 5y^2-4y-30=0 | | y^2-x^2-12y-8x-16=0 | | 16(x+1)-2(3-x)=-3(x+6) | | x+3+3(x+2)=9-2x | | 10x+4(-3x+1)-1=2x-(4x+1) | | 5+6(x+3)=4(x-1)+7 | | 4,6+z=5,6-3z | | 0,2x+2,5=1,5x-10,5 | | -y+2=-2y+0,5 | | 1,5p-2,3=-2,3+4p | | x^2dy-y^2dx=0 | | 9p+79= | | 2x-4=9x-28 | | 8x^2+x+63=0 |